Does stress alleviation always intensify plant-plant competition? A case study from alpine meadows with simulation of both climate warming and nitrogen deposition. (November 2022) - Wang, Jun; Zhang, Chunyan; Luo, Peng; Yang, Hao; Mou, Chengxiang; Mo, Li
Highlights: The SGH were tested at two alpine meadows of different habitats under either warming (W) or nitrogen addition (N). Beneficiary plants were two degradation indicator species. Neighbor effects on beneficiaries were different between habitats. W and N change neighbor effects differently. Stress type, plant strategy and natural intensity of neighbor effects may be important for further refinement of the SGH. Abstract: The effects of neighboring vegetation are important for plant fitness and community assembly under global change. What is less clear is how plant-plant interactions would change along the stress gradient. Our aim is to test the hypothesis that the abiotic stress alleviation induced by nitrogen (N) deposition and climate warming intensified the competitive effects of neighboring vegetation on two degradation indicator species of alpine meadows (i.e., Potentilla anserine and Ligularia virgaurea ), as predicted by the popular "stress-gradient hypothesis" (SGH). A neighbor removal experiment was conducted with either N addition or artificial warming as treatments at both an alpine mesophytic meadows site (MESms ) and a semi-hydric marsh meadows site (SHMms ) on the southeastern Tibetan Plateau. The net neighbor effects on both P. anserine and L. virgaurea were extreme and moderate competition in MESms, respectively, but were mild facilitation in SHMms . In line with the SGH, both N addition and warming intensified the neighbor competitive effects on L. virgaurea in MESms and weakened the neighbor facilitative effects on L. virgaurea in SHMms . However, in contrast to the SGH, the neighbor competitive effects on P. anserine in MESms were weakened by both N addition and warming. Furthermore, the neighbor facilitative effects on P. anserine in SHMms were weakened by N addition but were not changed by warming. These diverse plant interaction-environmental gradient relationships were likely induced by the joint effects of stress type, plant strategy in response to stress and natural intensity of neighbor effects. It may be helpful to take these factors into consideration for further refinement of the SGH.